1996
DOI: 10.1097/00042560-199609000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Clinical, Virological, and Immunological Signs of Progression in HIV-1-Infected Patients Receiving Active Anti-Interferon-α Immunization: A 30-Month Follow-Up Report

Abstract: Twenty-seven HIV-1-infected patients, 16 at early stage of disease and without concomitant antiretroviral therapy and 11 at more advanced stage of disease receiving antiretroviral therapy, have been followed since their enrollment, November 1992 and July 1993, respectively, in phase I/II studies to evaluate safety and immunogenicity of an anti-interferon-alpha (IFN-alpha) vaccine, aimed at modulating the impaired cytokine network in AIDS patients by counteracting IFN-alpha overproduction. We compared clinical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…51 Type 1 interferons (IFNs) have also been shown to increase CXCL12-and CCL21-mediated migration, 24 which may be relevant for HIV-1 pathogenesis as the levels of IFNs are elevated with disease progression. 54 Our finding of an increase in migration toward CXCL12, CXCL13, and CCL21 in HIV-1 patients with CD4 ϩ T-cell counts less than 350 cells/L may thus reflect polyclonal stimulation of B cells, either by CD40-CD40L interactions, by IFNs or via TLR signaling during HIV-1. Our findings suggest that there may be an altered migration profile of B cells during HIV-1.…”
Section: Cxcr5/cxcl13 In B Cells Duringmentioning
confidence: 67%
“…51 Type 1 interferons (IFNs) have also been shown to increase CXCL12-and CCL21-mediated migration, 24 which may be relevant for HIV-1 pathogenesis as the levels of IFNs are elevated with disease progression. 54 Our finding of an increase in migration toward CXCL12, CXCL13, and CCL21 in HIV-1 patients with CD4 ϩ T-cell counts less than 350 cells/L may thus reflect polyclonal stimulation of B cells, either by CD40-CD40L interactions, by IFNs or via TLR signaling during HIV-1. Our findings suggest that there may be an altered migration profile of B cells during HIV-1.…”
Section: Cxcr5/cxcl13 In B Cells Duringmentioning
confidence: 67%
“…In my view, these in vitro and in vivo results taken together, as well as animal experiments showing the safety and immunogenicity of inactivated Tat (35), are powerful arguments for clinical intervention. Indeed, they have already prompted a clinical therapeutic (33) and a preventive (34) vaccine study in humans utilizing a chemically detoxified but immunogenic Tat called Tat toxoid (33).…”
Section: Perspectivementioning
confidence: 98%
“…Preliminary results of these studies in immune deficient patients show safety and immunogenicity (33). These clinical trials were complemented by earlier and ongoing studies that utilized a preparation of inactivated IFN-␣ as a therapeutic vaccine, i.e., used only in infected individuals (35,36). As in the recent Tat studies, safety and immunogenicity were demonstrated, and CD4 ϩ T cell numbers were stabilized (35,36).…”
Section: Perspectivementioning
confidence: 99%
“…(ii) IL-2 secretion is another effector component of the cellular immune response by PBMC, and we have shown previously (11) that the decline in IL-2 secretion from activated T cells derived from AIDS patients is repaired partially in the presence of anti-IFN␣ Abs (11). (iii) High levels of circulating IFN␣ in AIDS patients are associated with a poor prognosis (41).…”
Section: Discussionmentioning
confidence: 99%